Kajian Strartegi Promosi Dan Strategi Penentuan Harga Tiket Masuk Museum Berdasarkan Sudut Pandang Pengunjung (Studi Empiris Di Kota Besar Di Pulau Jawa) - Rina Astini (Jurnal Manajemen, 2014)
This study is a follow-up study that examined the museum marketing phenomenon quantitatively. The decrease in the number of visitors to the museum is continuously in almost all museums on the island of Java and the museum visitor behavior became the focus of analysis in this study.